Exploring the Pathways: Good Corporate Governance, Intellectual Capital, and Financial Distress - Benny Oktaviano; Edi Triwibowo; Sindik Widati (Jurnal Riset Akuntansi, 2026)
Financial distress has become a critical issue for companies operating in highly competitive and capital-intensive industries, making effective corporate governance and the efficient utilization of intangible resources increasingly important for ensuring long-term financial sustainability. This study aims to examine the effect of Good Corporate Governance on Financial Distress and to investigate the mediating role of Intellectual Capital in this relationship. The research employs a quantitative explanatory approach using panel data from 23 energy and mining companies listed on the Indonesia Stock Exchange during the 2021–2024 period, resulting in 92 firm-year observations. Secondary data obtained from annual reports and financial statements were analyzed using descriptive statistics, classical assumption tests, panel regression analysis, and mediation analysis. The findings indicate that Good Corporate Governance has a significant negative effect on Financial Distress, suggesting that stronger governance practices improve financial stability and reduce the likelihood of financial difficulties. Intellectual Capital also demonstrates a significant negative effect on Financial Distress and partially mediates the relationship between Good Corporate Governance and Financial Distress. These findings imply that effective governance combined with the strategic management of intellectual resources enhances organizational resilience and supports sustainable corporate performance. The study contributes to the literature by integrating governance quality and intellectual capital into a single framework for explaining financial distress and provides practical insights for managers, investors, and policymakers in strengthening corporate sustainability.